Georreferenciamento de adolescentes com maloclusão em uma capital do sul do Brasil - Zortéa, Cristiano (2018)
Malocclusion is defined as an anomaly in the development of teeth and/or dental arches that shows some form of impact on the life of individuals affected by it. Overall, its prevalence is high worldwide. Early diagnosis is extremely important and enables interventions with simple measures and more affordable costs. Therefore, and in order to contribute to the discussion about the relevance of spatial analysis, this research is justified by the possibility of providing subsidies for the implementation of strategies to promote oral health. Thus, this study aimed to georeference the adolescents from 10 to 14 years old with malocclusion and to seek possible association with other variables. Possible explanations were sought for the spatial distribution of the disease. With a cross-sectional and quantitative design, secondary data were analyzed from a survey carried out in 2016 with 538 individuals randomized in public schools in the nine Health Districts (HD) from the city of Curitiba, PR, Brazil. The variables collected by questionnaire were: age (in years), gender (male/female) and HD (Matriz/Cidade Industrial de Curitiba (CIC)/Bairro Novo/Cajuru/Boqueirão/Boa Vista/Santa Felicidade/Pinheirinho/Portão). In the clinical examination, the participants were recorded in: with normal occlusion and with malocclusion (anterior open bite, anterior crossbite, posterior crossbite, deep bite, excessive overjet and anterior crowding). Initially the descriptive data analysis was performed, followed by the Chi-square test, with significance of 5%. The georeferencing and Kernel map were performed through the Quantum GIS program (QGIS) 2.18.3. The mean age was 11.2 years (SD = 1.2). Males comprised 49,3% of the sample, and females, 50.7%, and among the characteristics presented, there were more cases of deep bite (22.7%), while the previous crossbite was the least common (1.7%). The frequency of malocclusion was 52.4%, and among the presented characteristics, a greater prevalence of deep bite was observed (22.7%), while the less common was the anterior crossbite (1.7%). The malocclusion was not associated with sex (p = 0.389) and HD (p = 0.079). It was concluded that malocclusion had a high prevalence in the sample studied, but without effect of the place of residence. Georeferencing proved to be a useful tool for identifying the spatial distribution of the disease